Acompanhamento do controle de qualidade de produtos saneantes - Menezes, Isnara Victória Silveira de (Universidade Federal Rural do Semi-Árido, 2019)
According to Law no. 6,360 of September 23, 1976, household sanitizing products are defined as substances or preparations intended for household sanitation, disinfection or disinfestation in collective and / or public environments, in places of common use and in the treatment of water comprising insecticides, rodenticides, disinfectants and detergents. From the Latin, domus means "home" and sanitary means "cleaning", so the term household cleaning means "cleaning the home". However, these products are not only used in household cleaning, they are also applied in hospitals, industries, public environments and others. The body that regulates and supervises the sanitizing industries is the National Agency of Sanitary Surveillance (ANVISA), which has laws, decrees and resolutions that limit the use of substances harmful to man or the environment, as well as rules of production and suitability for the legalization of companies establishing conditions of infractions and their punishments. In addition, ANVISA requires companies to be responsible for developing products with strict quality control, which is extremely important. Indústria e Comércio de Sabão Guarani Ltda performs physical-chemical analyzes to ascertain the conditions of raw materials for the development of its products, which are: bar soap, laundry soap, dishwasher, disinfectant, softener, lava flooring, liquid wax. It is possible to have a follow-up and control of the changes that may occur in a production process through the control chart or control chart, indicating the situation of the process and whether it is in compliance with the statistical control.
Monografia
Keywords: Saneantes domissanitários; ANVISA; Sabão Guarani; Controle de qualidade; Análises físico-químicas; ENGENHARIAS::ENGENHARIA QUIMICA